Penafsiran Ayat-Ayat Jihad Dalam Kitab Al-Qur’an Al-‘Adzim Karya Ibnu Katsir - Abdur Razzaq; Jaka Perkasa (Wardah, 2019)
Abstract: This study aims to analyze the method of interpreting the verses of jihad carried out by Ibn Kathir in his book-Al-Qur’an Al-‘Adzim ’. The method used is to use a library study approach (libary research), by collecting qualitative data. two sources; primary and secondary. The primary source of the researcher is Al-'Azhim's Qur'anic Interpretation by Ibn Kathir, while secondary sources are obtained from books, journals, magazines and other sources whose uses are to enrich the material and as a comparison of primary sources . The data collection technique is to use documentation that is collecting various library books that have relevance to the title of this research, then analyzed by correlative analysis methods and descriptive relevance. The findings of this study are verses of jihad which are interpreted by Ibn Kathir tend to interpret jihad in the Qur'an as a war against the enemy to defend Islam. Conclusions about the importance of jihad and its privileges in Islam with concepts that are in accordance with Islamic sharia and in line with those outlined by the Qur'an and also explained by the Hadith of the Prophet Muhammad even though they do not cover in depth the language rules or derivatives of the word jihad in the Qur'an and does not discuss the issue of jihad in the realm of jurisprudence. Keyworld: Verse of jihad, Ibnu Katsir